The Effect of Earmuff and Earplug Use on Preterm Infants Towards Oxygen Saturation and Pulse - Deswinda Deswinda; Dini Maulinda; Bayhakki Bayhakki (JKP (Jurnal Keperawatan Padjajaran), 2022)
Background: A bright circumstance, cold temperature with loud noise where there are many activities around could influence baby’s sleep.